Legal Protection for Children as Victims of Criminal Acts of Sexual Intercourse Committed by People Who Have Family Relationships and Carried Out Continuously (Case Study of Decision Number: 49/Pid.Sus/2024/PN Mtw) - Situmeang, Ria Debora; Wahyuningsih, Sri Endah (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The crime of sexual intercourse with a child can be classified as an immoral crime that can damage the child's future. Article 82 Paragraph (1) Jo. Article 76 E of Law 23 of 2002 concerning Child Protection regulates the Act of Sexual Intercourse Against Children. The purpose of this study is to determine and analyze legal protection for children as victims of the crime of sexual intercourse committed by people who have family ties and are carried out continuously at the Muara Teweh District Court. To determine and analyze the obstacles and solutions to legal protection for children as victims of the crime of sexual intercourse committed by people who have family ties and are carried out continuously at the Muara Teweh District Court. The method used by the researcher is a normative legal aproach and the specifications in this study are descriptive analytical. The sources and types of data in this study are secondary data obtained from literature studies. The data is analyzed qualitatively using the theory of legal protection and the theory of legal effectiveness. Based on the results of the study, legal protection for child victims of sexual intercourse committed by people with ongoing family relationships in the Muara Teweh District Court is regulated in the Child Protection Law (Law Number 35 of 2014 concerning Child Protection) and related legislation. This law provides special protection through various efforts, including social rehabilitation, psychosocial assistance, and handling cases in juvenile courts. The criminal penalties imposed on the perpetrator are also increased if the act is carried out continuously or by the victim's parents. The penalties imposed for perpetrators of this crime are severe, and the juvenile justice system provides special protection to victims. Obstacles to legal protection for children as victims of sexual intercourse committed by people who have ongoing family relationships and carried out continuously in the Muara Teweh District Court are the lack of public awareness, the inability of law enforcement officers, and weak suport from family and the community. Solutions include: Increasing Education and Socialization, Training of Law Enforcement Officers, Increasing Suport from Family and the Community.